Analisis Faktor Faktor Pertumbuhan Ekonomi - Nurainun Putri; Ica Gunawan; Indah Wahyuni; Suhairi Suhairi (LPPM IAI Nasional Laa Roiba Bogor, 2021)
An important indicator of the success of development and the progress of a country is determined by Economic Development. Indispensable in analyzing government spending as well as several other variables as a measure of long-term economic growth in a country. Even in a country can be said to be able or not in solving a country's economic problems can be seen from the macroeconomic and microeconomic aspects of a country itself. The method used in this writing is the literature review method. Literature review reviews the scientific literature on an and critically analyzes, topics, and synthesizes research findings, theory, and practice. Economic growth is a change that is quantitative in nature and is usually measured using data on gross domestic product (GDP) or per capita production income at the previous year's real national level. the previous year's GDP variable had a positive effect on economic growth. This shows that the faster the convergence, the higher the economic growth. Keywords: Economic Growth Factors, PDB, Government.